Justifications of Intellectual Property Rights: A Discussion on Locke and Hegel's Theories - Muhamad Helmi Muhamad Khair; Haswira Nor Mohamad Hashim (Universitas Ahmad Dahlan, 2020)
Introduction to The Problem: At its core, Locke’s main argument is centralised in the role of labour, while Hegel’s principal idea lies in one’s will, self-actualisation as well as personal expression. As both thinkers posit strong arguments in substantiating their views, discussions surrounding this topic may influence one to favour a particular theory over the other.Purpose/Objective Study: This paper makes a modest attempt to discuss the justifications of intellectual property rights by focusing on two well-known philosophers, John Locke and G.W.F Hegel.Design/Methodology/Approach: The research design is exploratory as this paper aspires to explore the basis for the grant of intellectual property rights from the lenses of both theories. Therefore, the research methodology is purely doctrinal and theoretical. The research approach is mainly based on library research, focusing on a reading and analysis of Locke and Hegel’s published works, as well as other materials such as journal articles, commentaries, and textbooks.Findings: This article contributes to the existing body of knowledge by highlighting that neither Locke nor Hegel could provide one-fit-for-all justifications of intellectual property rights. Nevertheless, it is worth stating that both philosophers do contribute thoughtful insights that reflect important values worthy of considerations and should never be undermined when framing policies and laws on intellectual property rights.Paper Type: General Review